A UK-wide cross-sectional survey of practice exploring current trends in endometrial preparation for frozen-thawed embryo replacement. (15th March 2022) - Noble, Matt; Child, Tim
Abstract: In the United Kingdom, between 2012 and 2017 the annual number of frozen-thawed embryo replacement (FER) cycles doubled, while fresh cycles declined. With FER now accounting for 34% of IVF cycles, the aim of this UK-wide survey of IVF clinics was to determine current trends in the management of FER. A senior clinician in each of the 84 UK IVF clinics was asked to complete an online survey between September 2018 and February 2019 focussing on their clinic's first-line protocols for FER. Sixty-five clinics (77%) responded, accounting for approximately 24, 419 FER cycles annually. In ovulatory women, 69% of clinics favour medicated, 26% natural cycle and 5% modified natural cycle FER. In medicated FER, 61% of clinics undertake blastocyst transfer on the sixth day of progesterone administration, 21% on the fifth, 13% on the seventh, 3% on the fourth and 2% on the third. The preferred route of progesterone in medicated FER is vaginal, favoured by 82% of clinics. For pituitary suppression, 55% of clinics favour GnRH-agonist, 11% GnRH-antagonist and 34% oestrogen-only. In natural cycle FER, 31% always, 44% sometimes and 25% never give supplementary luteal support. In summary, the results illustrate wide variation in practice and highlight key research priorities.